Polar influences in radical reactions. Part VII. Hydrogen abstraction from nuclear-substituted diphenylmethanes, deoxybenzoins, and allylbenzenes by atomic bromine - Low, T.P.; Lee, K.H. (Royal Society of Chemistry, 1970)
The relative reactivities of nuclear-substituted diphenylmethanes, deoxybenzoins (X·C6H4·CH2Bz), and allylbenzenes towards atomic bromine at 80° have been determined by means of competitive reactions by use of allylbenzene, diphenylmethyl methyl ether, and p-bromoethylbenzene, respectively, as reference standard. The results show p-values of -0.93, -0.92, and -0.68 by the Hammett equation for the three systems, the first two systems being better correlated by σ-constants while in the third system σ+-constants gave better correlation in agreement with a previous report. The probable reasons for the correlation with σ-constants are discussed. The ρ-values for these systems fit in well with the consistent inverse relationship with the reactivity values previously observed.